Examples of mitigation strategies in the Dutch dairy sector - Vries, Marion de (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
"Examples of mitigation strategies in the Dutch dairy sector," presented by Marion de Vries (Wageningen UR) at the CCAFS project meeting with CAAS, CAU & WUR in Beijing, January 15th 2019.